2012
DOI: 10.1007/s12687-012-0085-1
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of autoimmune thyroid disease in the Lebanese population

Abstract: This study aims to investigate the association of human leukocyte antigen (HLA) class II genes and cytotoxic T lymphocyte-associated antigen-4 (CTLA-4) with autoimmune thyroid diseases in the Lebanese population. A total of 128 patients with autoimmune thyroid disease (55 with Graves' disease (GD) and 73 with Hashimoto's thyroiditis (HT)) were typed for HLA DQA1 (0301 and 0501) and DQB1 (0201, 0302, and 0303) and for 49A/G CTLA-4 using PCR-based sequence-specific priming methods. A total of 186 matched control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Our meta-analysis, including 2295 patients with HT and 4521 controls, investigated the association of A49G polymorphism with HT in all studies and in ethnicity and age subgroups from the 24 studies. We included 11 novel case-control studies (Balbi et al, 2007;Dallos et al, 2008;Yesilkaya et al, 2008;Yu et al, 2008;Bicek et al, 2009;Kucharska et al, 2009;Sahin et al, 2009;Shi et al, 2010;Benhatchi et al, 2011;Yang et al, 2012;Farra et al, 2012). Furthermore, we excluded studies when the genotype distribution in controls was not in HWE (Shi et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our meta-analysis, including 2295 patients with HT and 4521 controls, investigated the association of A49G polymorphism with HT in all studies and in ethnicity and age subgroups from the 24 studies. We included 11 novel case-control studies (Balbi et al, 2007;Dallos et al, 2008;Yesilkaya et al, 2008;Yu et al, 2008;Bicek et al, 2009;Kucharska et al, 2009;Sahin et al, 2009;Shi et al, 2010;Benhatchi et al, 2011;Yang et al, 2012;Farra et al, 2012). Furthermore, we excluded studies when the genotype distribution in controls was not in HWE (Shi et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Based on our search strategy, the primary screening produced 33 potentially relevant articles, of which 24 studies met the inclusion criteria after evaluating the association of the A49G polymorphism with HT [Donner et al, 1997;Awata et al, 1998;Kouki et al, 2000;Park et al, 2000;Petrone et al, 2001;Wang et al, 2001;Tomoyose et al, 2002;Terauchi et al, 2003;Ueda et al, 2003;Zhou et al, 2003;Balbi et al, 2007;Kavvoura et al, 2007 (a meta-analysis, which included 3 unpublished studies: Ban et al; Akazumi et al; Ghaderi et al); Dallos et al, 2008;Yesilkaya et al, 2008;Yu et al, 2008;Bicek et al, 2009;Kucharska et al, 2009;Sahin et al, 2009;Shi et al, 2010;Benhatchi et al, 2011;Yang et al, 2012;Farra et al, 2012]. In total, 2165 HT patients and 4284 controls were examined.…”
Section: Study Inclusion and Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, the +49A/G polymorphism in exon 1 results in a threonine-to-alanine conversion, which Gu et al showed to be associated with GD in the Chinese Han population [5]. By contrast, others found that the +49A/G polymorphism in exon 1 was irrelevant in the Japanese, Brazil and Lebanese populations [4, 6, 7]. Linkage analysis, candidate gene analysis and GWAS unanimously confirmed that the CD40–1 C/T polymorphism located at 20q11.2-20q13 was stably associated with GD susceptibility [8–10].…”
Section: Introductionmentioning
confidence: 99%